French Language Policies and the Revitalisation of Regional Languages in the 21st Century - Harrison, Michelle A.; Joubert, Aurélie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited volume presents an analysis of the evolution of French language policies and their impact on French regional languages and their communities. It gathers studies on language revitalisation from several territorial minority languages (Breton, Alsatian, Catalan, Occitan, Basque, Corsican, Francoprovençal, Picard, Reunionese) and evaluates the challenges and opportunities that they face in the 21st century. The chapters tackle different aspects of language endangerment and language planning and adopt varied theoretical and methodological approaches. The first section of the book reconsiders the difficulties in establishing linguistic boundaries and classification for some regional languages. The second section examines the important theme of the new generation of speakers with issues of transmission and identity formation and the changes they can bring to traditional communities. The third section highlights new developments in the context of new technologies and the heightened visibility of regional languages. Finally, the last section presents an overview of the contemporary situation of minority language revitalisation in France and synthesises the key trends identified in this volume: from the educational domain to the European Charter for Minority and Regional languages. This book will appeal to students and scholars of the sociology of language, sociolinguistics, language policy, minority languages and language endangerment. Michelle A. Harrison is Teaching Fellow in French Studies at the University of Leicester, UK. She has published on regional language-in-education policy and the evolution of language beliefs in Alsace. Aurélie Joubert is Lecturer in French Studies at Queen's University Belfast, UK. She has published on language endangerment and transnational speakers' attitudes in particular with respect to Occitan and Catalan.
Foreword: Regional language policy for a 21st-century Republic; Leigh Oakes -- Chapter 1: Introduction: Shifting dynamics in French language policies; Michelle A. Harrison and Aurélie Joubert -- Part I Reconsidering boundaries: languages, dialects and translingual practices -- Chapter 2: Linguistic Classification: The Persistent Challenge of the Langues d'oïl; Patrick Seán McCrea -- Chapter 3: Opposition to the process of language identification and standardisation in 'Limousin Occitan' and 'Poitevin-Saintongeais'; Jean-Christophe Dourdet -- Chapter 4: Challenging diglossic models: Translingual practices in La Réunion; Natalia Bremner -- Part II New dynamics in the communities: transmission, identity relations and the emergence of new speakers -- Chapter 5: Evolution of linguistic identity in a super-region: the case of Catalans and Occitans in Occitanie; Aurélie Joubert -- Chapter 6: Diffusion and transmission of Francoprovençal: A study of speakers' linguistic conscience; Giovanni Depau -- Chapter 7: On new speakers and language revitalisation: Arpitan and community (re)formation; Jonathan Kasstan -- Part III The perception of regional languages: visibility and modernity -- Chapter 8: Gastronomy, Football, and Resistance: The multi-faceted visibility of Corsican in the Linguistic Landscape; H. William Amos -- Chapter 9: Picard in the digital world: A language that is seen; Jean-Michel Eloy, Fanny Martin and Cécile Mathieu -- Chapter 10: Publishing in a regional language: the case of Breton in the 21st century; Hervé Baudry -- Part IV The long-term impact of French public policy and the resistance to the European Charter for Regional or Minority Languages -- Chapter 11: Public language policy and the revitalisation of Basque; Jean-Baptiste Coyos -- Chapter 12: The evolution of regional language maintenance in southern Alsace and Northern Catalonia: A longitudinal study of two regional communities; Judith Broadbridge and Dawn Marley -- Chapter 13: The influence of teachers' language attitudes on classroom practices in Alsace; Michelle A. Harrison -- Chapter 14: The langues de France and the European Charter for Regional or Minority Languages: keeping ratification at bay through disinformation - 2014-2015; Geoffrey Roger -- Chapter 15: Epilogue; Robert J. Blackwood.
Keywords: Language policy; Sociolinguistics; Europe -- Politics and government; Political planning; Philosophy of mind; Self; Language Policy and Planning; Sociolinguistics; European Politics; Public Policy; Philosophy of the Self